(untitled) (Journal of the College of Education for Women, 2019)
The City of Ember is a very interesting novel that is although intended for young readers, have so many layers and messages that are misunderstood. In this research, both the novel and the film adaptation are studied with the intent to decode the warning messages that the novelist and the director tried to introduce to the audience. The research studies four vital messages; the first message is that history repeats itself for the novel has many allusions to the history of Jews and their painful holocaust and even goes back in history the days of Moses and the Exodus, the second message tackles the conspiracy theory that states nothing happens by accident and that everything is planned and connected hence comes the third message incarnated in the film adaptation of the novel, secret societies do exist namely the freemasons. Finally, the four messages come like a rather dark omen, Man’s internal fear of the end whether the religious end represented by the apocalypse or the scientific end and the expiry of earth. Since the novel is for young readers, the author has provided a silver lining at the final message stating people always find a solution for all their problems in spite of the chronic fear.